Selective recovery and purification of carotenoids and fatty acids from Rhodotorula glutinis using mixtures of biosolvents - Mussagy, Cassamo U. [UNESP]; Remonatto, Daniela [UNESP]; Paula, Ariela V. [UNESP]; Herculano, Rondinelli D. [UNESP]; Santos-Ebinuma, Valéria C. [UNESP]; Coutinho, João A.P.; Pereira, Jorge F.B. (Elsevier, 2021)
Selective recovery and purification of carotenoids and lipids from oleaginous red yeast Rhodotorula glutinis require a complex integration of different downstream operations. Envisioning a future industrial application in the bioeconomy framework, an experimental planning was used to design ternary mixtures of bio-based solvents (biosolvents) for simultaneous recovery and selective separation of carotenoids (i.e., β-carotene and torularhodin) and fatty acids (i.e., margaric acid, stearic acid and pentadecylic acid) from untreated (fresh wet) and freeze/thaw pre-treated (wet and dry) biomass of Rhodotorula glutinis CCT-2186. Two ternary systems of biosolvents, (i) ethanol:ethyl lactate:water and ii) ethanol:ethyl acetate:water, were investigated in solid–liquid extraction procedures to permeabilize/disintegrate the yeast cells and to enhance the selective recovery of β-carotene, torularhodin and fatty acids from the intracellular environment. Optimization of the ternary mixture composition for recovery of carotenoids and fatty acids from the three types of biomass allowed to obtain yields higher than 75% (w/w) from pre-treated dry biomass using mixture of ethanol:ethyl acetate:water (67:33:00% w/w/w). The best systems were then integrated with a liquid–liquid extraction for the selective separation of carotenoids and fatty acids and solvent recycling. The mixtures of biosolvents were reused up to three consecutive extraction cycles, maintaining high extraction efficiency yields of both carotenoids (>45% w/w) and lipids (>30% w/w). At the end, the biological activity of the carotenoids extracts was confirmed by determining the antioxidant activity using Electron Paramagnetic Resonance (EPR) and the stable free radical 1,1‐diphenyl‐2‐picrylhydrazyl (DPPH·). The highest antioxidant activity (93%) was obtained with torularhodin (250 μg/mL). This study confirms that extraction platforms using mixed biosolvents are simple, efficient and sustainable solutions for the selective recovery and separation of carotenoids and fatty acids from microbial biomass.
Keywords: Antioxidant; Biosolvent; Carotenoid; Extraction; Fatty acids; Rhodotorula glutinis